Business Model Innovation of Selected Textile Company - Mammadov, Toghrul; Kubíček, Aleš; Kupec, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor thesis covers the business model innovation (BMI) for a newly launched private textile company called "Battido," which currently focusing on using social networks for sales. he project will cover the Business Model Canvas (BMC) for analysing and refining Battido's business strategy, including the macro and microeconomic factors, internal analysis, and a new marketing plan, incorporating the SWOT and PEST analyses. In the practical part, these strategic analytical tools aim to enhance the company’s market competitiveness and demonstrate the challenges and competitive advantages of “Battido” by aligning technological advances, customer needs / preferences, and current economic conditions in the home country where the business is operating. In conclusion, the results demonstrating that dynamics, responsive approach to BMI, integrated with digital marketing strategies and e-commerce, can significantly enhance “Battido’s market position and sustainability.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses